Lumbung as critique of arts' discourse of economy and work - Keys, Thomas Ragnar Bronner (Nanyang Technological University, 2022)
This dissertation figures the forthcoming edition of Documenta as a primary, though not exclusive, vector of analysis in ongoing debates on the political economy of the art field and anticipates some of the implications and effects this edition will have on contemporary Curatorial practices and the exhibition-specific economies and discourses they engender. How do procedural interventions into the various processes of capital accumulation, from within Contemporary Art and Exhibition Histories, interact with the lived political economy that dictate the material and disciplinary conditions of those practices? The appointment of ruangrupa as Artistic Directors of documenta fifteen (2022), and their subsequent implementation of a transnational share-economy within it, is a significant departure from the standard legal-economic conditions and arrangements of global practices of exhibition making. My positions, criticisms and considerations are anchored by historical vignettes from previous editions of Documenta, practices and arguments associated with Institutional Critique and current writing on the Curatorial in Southeast Asia. The paper utilizes existing literature on ruangrupa’s and Documenta’s distinct histories, promotional media and art journalism pertaining to documenta fifteen as well insights from conversations with relevant parties and further select critical literature on contemporary arts’ discourses of labor and economy. The selection of documenta fifteen as the central case study is not be understood singularly but instead as an exemplary model projected to contain findings and developments applicable to other calls to restructure the legal-economic arrangements of exhibitions from within the curatorial discipline. Further, this paper reflects critically on the still-unfolding processes guiding and establishing the terms through which contemporary art practices from Southeast Asia are being presently incorporated into the mainstream Euro-American field of Art.